Detection of Actinobacillus actinomycetemcomitans DNA in Patients with Partial and Complete Dentures by Real-Time PCR - Enis Veseli; Gloria Staka (International Journal of Biomedicine, 2023)
Background: The purpose of the present study was to detect Actinobacillus actinomycetemcomitans (Aa) using RT-PCR in patients with complete and partial edentulism before (T0) and three months after (T3) treatment with removable partial dentures (RPD) and complete dentures (CD), respectively, to compare the data between these two research groups. Methods and Results: The sample comprised 60 patients: 33 men and 27 women, aged 48 to 76 years. The patients were divided into two groups. Group 1 included 30 patients with partial edentulism who were treated with RPD. Group 2 included 30 patients with complete edentulism who were treated with CD. The samples from Group 1 were taken from the gingival sulcus of the abutment teeth by means of sterile paper points. For Group 2, the samples were taken with a sterile swab from the dorsum of the tongue. The samples were taken in T0 and T3 intervals. To detect Aa DNA, we used RT-PCR and ParodontoScreen REAL-TIME PCR Detection Kit (DNA-TECHNOLOGY). Bacterial load levels of species were conventionally represented in logarithm (Lg) of genome equivalents per sample. The results were also presented in three ranges depending on the level of bacterial load: normal (< 4.0Lg), light/moderate (≥4.0 Lg), and severe (>5.0 Lg). The study found a significant difference in the amount of Aa between the T0 and T3 intervals only in patients treated with RPD (0.871.58 Lg vs. 1.28 1.96 Lg, P=0.004). Patients treated with CD, however, did not differ significantly in the amount of Aa between the T0 and T3 intervals (0.030.16 Lg vs. 0). The average bacterial load in patients with RPD was significantly higher than in those with CD three months after treatment (P=0.02) (Table 2). The range of bacterial load levels in the groups is presented in Table 3. Of the 30 patients with RPD, 2(6.7%) had a severe range, 2(6.7%) had a mild/moderate range, and 26(86.7%) had a normal range. The 30 CD patients all had a normal range. There was no significant difference in the prevalence range of bacterial load level with Aa between groups (Fisher's Exact Test = 3.537, P=0.113) / Monte Carlo Sig. (2-sided) / 0.105–0.121). However, in general, RPD causes a significant increase in Aa, so the level of periodontal pathogens may be higher in RPD patients than in CD patients.